Improving Elementary School Students’ Vocabulary Mastery Using Wordwall Game - Safitri, Maya; Nadia, Hafizhatu; Aflahah, Noor Aida (Universitas Muhammadiyah Mataram, 2025)
Wordwall, are effective resources for English teachers to improve vocabulary acquisition in EFL classrooms. However, However, limited research has been conducted to explore the effectiveness of Wordwall in enhancing English vocabulary acquisition.This study attempted to increase the vocabulary mastery of elementary school students in terms of both vocabulary knowledge and pronunciation through the use of Wordwall game. Students in the fourth grade at an elementary school in Banjarmasin participated in the research. This study included 29 students as its subjects. This study was a two cycle Classroom Action Research (CAR) in collaborative with the English teacher. Four research processes were conducted in each cycle: planning, acting, observing, and reflecting. The research’s instruments were field notes, which were examined by qualitative and students’ test results which were examined by quantitative. The results proved that Wordwall game engagement improved students’ vocabulary mastery. It revealed how students’ pre and post-test results had improved. Students’ mean scores on the pre-test were 45,17 for pronunciation and 58,10 for vocabulary knowledge. Students’ mean scores on the post-test were 74,1 for pronunciation and 83,8 for vocabulary knowledge. The results of this study also shown how other strategies, such as using pictures and small group discussion might enhance the efficiency of the learning process. The authors recommended doing more research on the usage of Wordwall game to improve students’ English proficiency in addition to their vocabulary mastery. By implementing Wordwall game, the author can also discover additional techniques and classroom management that could optimize students’ learning outcomes.